Meneropong Urgensi Partisipasi Imam dalam Katekese di Media Sosial - Maurinus Reymino Naban; Edison Tinambunan (Publisher STPKat, 2025)
This paper focuses on examining the participation of priests through catechesis on social media. In this paper will be described the concrete steps of the priest in developing and growing the faith of Christians in this day and age. This paper finds that the participation of priests through social media is an important and urgent effort for the development and development of the people's faith. This is considered important, because in this day and age, the faithful are directly in the scope of social media whose development is difficult to stem. Be aware of it. This study seeks to remind priests to return to the nature of the ministry as priests through one concrete step, namely catechesis to Christians. Catechesis is a relevant tool in maintaining, growing and strengthening the faith of the people. The concrete way that can be done is to conduct activities to introduce the Holy Scriptures, and pray with the Holy Scriptures in lectio divina activities, and provide liturgical education. All these activities are done through social media. This concrete step is considered to be very helpful for the growth and maturity of faith. The research method used is literature analysis. The results of this study in the form of increasing the spirit of real participation of the priest for the life of the faith of the people, well maintained Christian faith in the midst of the challenges of increasingly rapid technological development, until it comes to the maturity of the perfect faith.